2019
DOI: 10.5194/acp-19-15007-2019
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation from OH-initiated oxidation of <i>m</i>-xylene: effects of relative humidity on yield and chemical composition

Abstract: Abstract. The effect of relative humidity (RH) on secondary organic aerosol (SOA) formation from the photooxidation of m-xylene initiated by OH radicals in the absence of seed particles was investigated in a Teflon reactor. The SOA yields were determined based on the particle mass concentrations measured with a scanning mobility particle sizer (SMPS) and reacted m-xylene concentrations measured with a gas chromatograph–mass spectrometer (GC-MS). The SOA components were analyzed using a Fourier transform infrar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…Increasing the RH shis the reaction equilibrium to small compounds, thereby suppressing oligomer formation. The negative effect of RH on SOA formation from the m-xylene photooxidation system without seed particles was also observed by Zhang et al 32 They suggested that both the faster wall losses of organic vapors and the shis of oligomer equilibrium reactions to monomers under higher RH condition can lead to the decrease in apparent m-xylene SOA yields. In marked difference to the ndings of Hinks et al, the mass concentrations of toluene SOA generated with inorganic seed particles were generally higher under higher-RH conditions due to the occurrence of aqueous-phase reactions in certain studies.…”
Section: Relative Humiditysupporting
confidence: 61%
See 3 more Smart Citations
“…Increasing the RH shis the reaction equilibrium to small compounds, thereby suppressing oligomer formation. The negative effect of RH on SOA formation from the m-xylene photooxidation system without seed particles was also observed by Zhang et al 32 They suggested that both the faster wall losses of organic vapors and the shis of oligomer equilibrium reactions to monomers under higher RH condition can lead to the decrease in apparent m-xylene SOA yields. In marked difference to the ndings of Hinks et al, the mass concentrations of toluene SOA generated with inorganic seed particles were generally higher under higher-RH conditions due to the occurrence of aqueous-phase reactions in certain studies.…”
Section: Relative Humiditysupporting
confidence: 61%
“…Over the past few decades, many efforts have been made to investigate the mass yield of aromatic SOA (the ratio of the mass of SOA generated to the mass of precursors consumed) and its formation mechanism. [31][32][33][34][35][36][37] However, the reported yields and formation mechanism of aromatic SOA remain highly variable even for a specic MAH. This variability can be attributed to the differences in the complex environmental conditions including physical parameters (i.e., solar intensity, temperature, and relative humidity (RH)), 32,35 inorganic pollutant emissions (i.e., nitrogen oxides (NO x ), ammonia, and sulfur dioxide (SO 2 )), 31,33 and reactant properties (VOC and oxidant concentrations as well as VOC structure).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike inorganic aerosol (i.e., SIA) formation, which favors humid conditions (Liu et al., 2018), observed SOA concentrations at Seoul during KORUS‐AQ show a negative relationship with relative humidity (RH; Figure S3 in Supporting Information ). Observational studies found that photochemistry was suppressed under high RH conditions, and larger anthropogenic SOA mass loadings and yields were observed with lower RH due to increased formation of oligomers in the absence of seed particles (Hinks et al., 2018; Liang et al., 2019; Liu et al., 2019; Zhang et al., 2019). Total PM loading and inorganic aerosol concentrations were particularly low during this period (Figure S2 in Supporting Information ), providing a less‐favorable condition for particle growth onto existing aerosols.…”
Section: Model Evaluation During Korus‐aqmentioning
confidence: 99%